2019
DOI: 10.1101/651240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

eIF3 associates with 80S ribosomes to promote translation elongation, mitochondrial homeostasis, and muscle health

Abstract: eIF3 is a multi-subunit complex with numerous functions in canonical translation initiation, including mRNA recruitment to the 40S ribosome, scanning for the start codon, and inhibition of premature 60S subunit joining 1-3 . eIF3 was also found to interact with 40S and 60S ribosomal proteins and translation elongation factors 4 , but a direct involvement in translation elongation has never been demonstrated. Using ribosome profiling, we found that eIF3 deficiency reduced early ribosomal elongation speed betwee… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Importantly, the TCRA and TCRB mRNA 3'-UTR elements are necessary and sufficient to control this burst in translation (Figure 3). Recent evidence suggests that eIF3 can remain associated with translating ribosomes (Bohlen et al, 2020;Lin et al, 2019;Wagner et al, 2020), a phenomenon that seems to be enhanced for the pan-mRNAs identified here. Additional layers of translation regulation also contribute to T cell function (Tan et al, 2017), particularly with respect to mTOR signaling (Miyamoto et al, 2005;Myers et al, 2019) and carbon metabolism (Manfrini et al, 2017;Ricciardi et al, 2018).…”
mentioning
confidence: 52%
“…Importantly, the TCRA and TCRB mRNA 3'-UTR elements are necessary and sufficient to control this burst in translation (Figure 3). Recent evidence suggests that eIF3 can remain associated with translating ribosomes (Bohlen et al, 2020;Lin et al, 2019;Wagner et al, 2020), a phenomenon that seems to be enhanced for the pan-mRNAs identified here. Additional layers of translation regulation also contribute to T cell function (Tan et al, 2017), particularly with respect to mTOR signaling (Miyamoto et al, 2005;Myers et al, 2019) and carbon metabolism (Manfrini et al, 2017;Ricciardi et al, 2018).…”
mentioning
confidence: 52%
“…13a ). Recent evidence suggests that eIF3 can remain associated with translating ribosomes 34,35,36 a phenomenon that may be enhanced for the pan-mRNAs identified here. Notably, additional layers of translation regulation also contribute to T cell function 37 , particularly with respect to mTOR signaling 3, 38 and carbon metabolism 4, 39 .…”
mentioning
confidence: 68%
“…While this manuscript was in preparation, a seminal selective 40S/80S ribosome footprinting work from the Teleman's lab revealed that scanning in majority of tested human cell lines occurs in a cap-tethered way and that eIF4G1 and eIF4E components of human eIF4F remain bound to 80S ribosomes during an early elongation phase (with a decay half-length of ∼12 codons) ( 17 ). Since these authors together with the Wolf's lab and us expectedly demonstrated that, besides the eIF4F factors, early human elongation complexes also carry eIF3 ( 12 , 16 ), and earlier evidence suggested an active involvement of mammalian eIF3, eIF4G and eIF4A in promoting REI ( 15 , 22 ), they proposed a simple model explaining the molecular basis of REI in mammals. It postulates that since majority of mammalian uORFs are believed to be permissive for REI ( 6 , 35 , 36 ), the fact that the cap-tethered eIF4F complex and eIF3 are temporarily retained on 80S ribosomes as they translate short uORFs suffices to prevent full ribosomal recycling and allow prompt assembly of the post-termination 48S complex.…”
Section: Discussionmentioning
confidence: 98%